2002
DOI: 10.1159/000063161
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Expression of Tumor Suppressor p16<sup>INK4</sup> Protein in Human Primary Gastric Cancer Is Related to the Grade of Differentiation

Abstract: Background: Recent research has revealed a rapid increase in the number of alterations underlying oncogenesis and the proteins which regulate the cell cycle. p16 is a cell cycle regulatory protein acting as a cyclin-dependent kinase inhibitor (CDKI). Because of its antiproliferative effect, p16 has been suggested to be a tumor suppressor gene. Deletions, mutations and functional inactivation of p16 occur with a frequency second only to p53 in most human malignancies. Aim: to evaluate the p16 protein expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
1
9
1
Order By: Relevance
“…Concerning to Lauren histological type, against expectations the diffuse type was predominant, 1,[26][27][28] no statistical difference between Lauren histological type and p16 expression in the two thresholds studied was found as previously reported, 12 although no agreement on this issue have been reached 7,27 . Although it is known that tumours with p16 loss tend to have a higher metastatic potential immunohistochemistry to p16 in lymph nodes was not carried out in this study, since overall p16 expression is much lower in metastatic lymph nodes than in primary lesion 6 .…”
Section: Results Results Results Resultssupporting
confidence: 46%
See 2 more Smart Citations
“…Concerning to Lauren histological type, against expectations the diffuse type was predominant, 1,[26][27][28] no statistical difference between Lauren histological type and p16 expression in the two thresholds studied was found as previously reported, 12 although no agreement on this issue have been reached 7,27 . Although it is known that tumours with p16 loss tend to have a higher metastatic potential immunohistochemistry to p16 in lymph nodes was not carried out in this study, since overall p16 expression is much lower in metastatic lymph nodes than in primary lesion 6 .…”
Section: Results Results Results Resultssupporting
confidence: 46%
“…Expression of p16 is decreased in node metastasis 6 . Apparently there is no difference in expression between intestinal and diffuse-type gastric adenocarcinoma 12 …”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, the correlation of loss of p16 protein expression with the cellular differentiation of HCC and gastric cancer has been reported [23,24] . Park et al also noted that inactivation of p16 exon 1 by DNA hypermethylation occurred during the progression of tumor cells to poorly differentiated HCC, which was induced by diethylnitrosamine plus thioacetamide in Fischer 344 rats [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on (distal) gastric carcinogenesis have shown a similar p16 'overexpression' in gastric carcinomas [16,17] with weak staining in non-involved mucosa. However, a recent immunohistochemical study found a progressive p16 decrease and a pRb increase from gastritis to dysplasia [12] in samples from the cardia.…”
Section: Discussionmentioning
confidence: 51%